2019
DOI: 10.14569/ijacsa.2019.0100861
|View full text |Cite
|
Sign up to set email alerts
|

Novel Adaptive Auto-Correction Technique for Enhanced Fingerprint Recognition

Abstract: Fingerprints are the most used biometric trait in applications where high level of security is required. Fingerprint image may vary due to various environmental conditions like temperature, humidity, weather etc. Hence, it is necessary to design a fingerprint recognition system that is robust against temperature variations. Existing techniques such as automated and non-automated techniques are not real time analysis (adaptive). In this paper, we propose an adaptive auto correction technique called Reference Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…A total of 250 fingerprint templates from 10 individuals were gathered at 25°C to 0°C for analysis. The trial results showed that applying the auto-correcting technique increased the rate of identification by 40% (161).…”
Section: E Fingerprint Biometric System Performance Improvement Techn...mentioning
confidence: 99%
“…A total of 250 fingerprint templates from 10 individuals were gathered at 25°C to 0°C for analysis. The trial results showed that applying the auto-correcting technique increased the rate of identification by 40% (161).…”
Section: E Fingerprint Biometric System Performance Improvement Techn...mentioning
confidence: 99%